The Role of Human Resource Management in Improving Teacher Professionalism and Education Quality - Lailatus Sari`atul Mahmudah; Nurul Hikmah; Muhammad Nazmul Hoque (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This writing aims to introduce and describe the application of HR management through planning, recruitment, selection, training, and development as well as performance evaluation metrics at MA Negeri Demak, including obstacles in the implementation of HR management MA Negeri Demak. Qualitative methods were used in writing this article. Based on the results of data analysis, it is known that the implementation of HR management in MA Negeri Demak is carried out well, the preparation of HR planning calculations, personnel are professional and transparent, the implementation of HR is quite professional. selection of resources, implementation of induction and professional training by considering school needs and qualifications of employees or teachers or teaching staff, implementation of training activities for planned development, and performance evaluation. Factors inhibiting the implementation of staffing: low welfare of teachers and honorary staff, lack of career clarity, lecturers are often late for teaching, and guaranteed quality of teaching.